A longitudinal test of the revised strain theory - Agnew, Robert (Journal of quantitative criminology, 1989)
Agnew's (1985) revised strain theory argues that delinquency results from the inability to escape legally from painful or aversive situations. There is much indirect support for the theory, with experimental and survey data indicating that delinquency is associated with a wide variety of aversive situations. The experimental data, however, are of questionable generalizability and the survey data are primarily cross sectional in nature, leaving unresolved the issue of causal direction. This study examines the relationship between environmental adversity and delinquency using longitudinal data from a nationally representative sample of adolescent boys. A distribution-free method (arbitrary generalized least squares) is used to estimate a covariance structure model depicting a reciprocal relationship between adversity and delinquency. The results support the revised strain theory: environmental adversity has a causal effect on delinquency, but delinquency does not have an effect on adversity.